Identification of Chromosomally Integrated Human Herpesvirus 6 by Droplet Digital PCR. (1st May 2014) - Sedlak, Ruth Hall; Cook, Linda; Huang, Meei-Li; Magaret, Amalia; Zerr, Danielle M; Boeckh, Michael; Jerome, Keith R
Abstract: BACKGROUND: Human herpesvirus 6 (HHV-6) latently infects a majority of adults. In about 1% of the population HHV-6 exists in a chromosomally integrated form (ciHHV-6) that resides in every somatic and germ cell and can be transmitted through the germ line. Patients with ciHHV-6 have been misdiagnosed and unnecessarily treated for active HHV-6 infection, sometimes with important side effects, based on results from quantitative molecular HHV-6 tests. METHODS: A droplet digital PCR (ddPCR) assay was developed to identify ciHHV-6 in cellular patient samples by precisely determining the ratio of HHV-6 to cellular DNA. We validated the assay on confirmed ciHHV-6 patient samples and a cell line derived from a ciHHV-6 patient, and we analyzed hematopoietic stem cell transplant patients suspected of having ciHHV-6. We additionally evaluated whether the assay could be applied to stored plasma samples from a study of clinical correlates of HHV-6. RESULTS: The ddPCR assay accurately identified ciHHV-6 in cellular samples (buffy coat, peripheral blood mononuclear cells), giving a ratio very close to 1 HHV-6/cell [mean (SD), 1.02 (0.03)] in fluorescence in situ hybridization–confirmed sample). In stored plasma samples, the assay performance was set by design to have 100% sensitivity, which resulted in 82% specificity for ciHHV-6. CONCLUSIONS: The possibility of ciHHV-6 is often overlooked in patients with detectable HHV-6 viral loads by quantitative PCR. Our ddPCR test provides rapid and accurate laboratory identification of ciHHV-6 from easily obtained cellular samples. In addition, the assay provides excellent sensitivity and specificity using stored plasma samples, facilitating retrospective analysis of the clinical significance of ciHHV-6.